Hubungan Pengetahuan Kesehatan Alat Reproduksi dengan Kejadian Kandidiasis Vulvovaginalis pada Penderita Kandidiasis Vulvovaginalis - Bahupati, Okky Wellianasari; , dr. Nurrachmat Mulianto, M.Sc., Sp.K.K; , dr. Ratih Pramuningtyas, Sp.KK (2015)
Background. Vulvovaginal candidiasis (VVC) is fungus that is located in the membrane of vagina which is cause by genus Candida albicans. This fungus is a normal flora that grew in human‟s body, however it also could occurs to be a pathogen and caused illness if there is a predisposition factor. One of the predispotition factor that caused the VVC is the lack of reproductive health. Objective. This research is to know and determine the relationship between the knowledge of reproductive health with the occurance of vulvovaginal candidiasis to the patient of VVC. Method. The type of method that are used in this research are by analytic observational with cross sectional approach. The amount of the sample that are used is 40 samples, and the data that are been collected are using the primary data which has been collected by questionnaire. Result. This research shows that there is a meaning relationship with the value of P = 0,000 which mean 0,000 < 0,1 and by that, it concludes that there are a relationship science of reproduction health with the occurance of vulvovaginal candidiasis. Conclution. There are a relationship between the science of reproduction health with the occurance of vulvovaginal candidiasis to patient of vulvovaginal candidiasis.